Polysialic acid is upregulated on activated immune cells and negatively regulates anticancer immune activity - Drummond-Guy, Olivia; Daly, John; Wu, Angeline; Stewart, Natalie; Milne, Katy; Duff, Chloe; Nelson, Brad H.; Williams, Karla C.; Wisnovsky, Simon (Frontiers in Oncology, 2025)
Suppression of anticancer immune function is a key driver of tumorigenesis. Identifying molecular pathways that inhibit anticancer immunity is critical for developing novel immunotherapeutics. One such molecule that has recently been identified is the carbohydrate polysialic acid (polySia), whose expression is dramatically upregulated on both cancer cells and immune cells in breast cancer patient tissues. The role of polySia in the anticancer immune response, however, remains incompletely understood. In this study, we profile polySia expression on both healthy primary immune cells and on infiltrating immune cells in the tumour microenvironment (TME). These studies reveal polySia expression on multiple immune cell subsets in patient breast tumors. We find that stimulation of primary T-cells and macrophages in vitro induces a significant upregulation of polySia expression. We subsequently show that polySia is appended to a range of different carrier proteins within these immune cells. Finally, we find that selective removal of polySia can significantly potentiate killing of breast cancer cells by innate immune cells. These studies implicate polySia as a significant negative regulator of anticancer immunity.